Students’ Virtual Classroom Experiences in the Post COVID-19 Era in Nigerian Universities - Ajadi, Olugbenga; Adebakin, Azees; Akinniranye, Oluwarotimi (COMPETITIVE: Journal of Education, 2025)
The global economy, health, and education—especially university education—have all been severely impacted by the COVID-19 pandemic. It exposed the seeming disparity and current injustices in the global north and south's access to quality education. Therefore, this study examined the desire of students to attend classes virtually in the post-COVID-19 era; identified perceived difficulties faced by students in online learning environments; and established favoured method of education delivery by students in the post-COVID-19 period. These were with a view to explore university students’ experiences during the COVID-19 outbreak. Using the quantitative survey approach, the study population covered 35,000 undergraduate and graduate students while a sample size of randomly selected 375 students was determined using the research advisor. A 25-item electronic google survey titled ‘Post COVID-19 University Education’ (PCUE) was designed and circulated via various students’ platforms on social media (WhatsApp and Telegram) to elicit responses. The research questions were analysed and presented descriptively. It was found that students at universities favour blended learning methods have difficulties that prevent them from participating in virtual classes, and do not frequently visit virtual classrooms. Consequently, it was recommended that university instructors be further encouraged to use the hybrid mode of instructional delivery.